Cold reactive collisions between neutral molecules and trapped ions - Petralia, L (2018)
This thesis describes the development and demonstration of techniques for the study of ion-neutral reactive collisions at low temperatures conducted using two unique experimental apparatuses comprising radio-frequency Paul traps. One apparatus combines a Stark decelerator with a Paul trap; the other apparatus features a buffer gas cell interfaced with a Paul trap through an electrostatic quadrupole guide. A novel ion trap time-of-flight mass spectrometer has been introduced and characterised. This apparatus is designed to detect the ion products of reactive collisions at low temperatures (< 10 K). This detection approach affords excellent detection efficiency and is broadly applicable to all ion-molecule reactions that one could study within a linear Paul ion trap. A proof-of-principle reaction between xenon ions and neutral ammonia isotopologues is examined to test the performance of the new detection set-up. With the goal of achieving full control over the reaction parameters, the amount of alignment retained by rotationally and translationally cold ammonia molecules exiting the electrostatic guide has been examined using (2 + 1) REMPI detection of the molecules with varying linear polarisation. Simulations suggests how modifications to the current setup will enable full orientation of the cooled molecules reaching the detection region to be achieved. Experiments on cold charge exchange reactions between sympathetically-cooled Xe+ and room temperature ammonia (NH3 and ND3) have been conducted within lasercooled Ca+ Coulomb crystals in a linear Paul ion trap. There is ongoing work to ascertain any difference in reactivity between NH3 and ND3 as the neutral reactant species. Preliminary data are discussed at a qualitative level, with the prospect of observing any isotope effect in this charge transfer process. Charge exchange reaction experiments using cold state-selected ammonia are discussed with the goal of establishing reaction rate constants at different collision energies.